NURSING STAFF COMPETENCIES AT INNOVATIVE CARE FACILITIES FOR PEOPLE WITH DEMENTIA. (11th November 2018) - De Boer, B; Buist, Y; de Bruin, S R; Hamers, J P H; Verbeek, H
Abstract: The shift towards psychosocial care for people with dementia leads to innovative care facilities such as green care farms (GCFs), paying particular attention to residents' quality of life, meaningful activities and homelike environments. Working in these settings likely requires different competencies compared with traditional facilities. To obtain insight into which competencies are important for working in GCFs, small-scale facilities or traditional facilities and to assess whether there are differences between the facilities, semi-structured interviews with nursing staff (n=19) and managers (n=23) were held. At GCFs, creativity, flexibility, and respectfulness were mentioned most often. Respondents from GCFs and small-scale facilities had an evident focus on autonomy and well-being of residents rather than on technical nursing skills. At traditional facilities, managers also had this focus, yet this was not in line with the views of their nursing staff. Thus, there was better alignment between staff and managers at GCFs and small-scale facilities.